3ds max 7 Bible - Murdock, Kelly L. (Wiley Publishing, 2011)
* Packed with expert advice, timesaving tips, and more than 150 step-by-step tutorials, this book is a must for anyone who wants to master this complex, expensive software package * Offers full coverage of new software features and enhancements and shows users how to master everything from the Particle Flow interface and architectural objects and materials to Shockwave 3D Export and VertexPaint features * The companion CD-ROMs include a demo version of the new 3ds max, tutorial files, 3D models, bonus plug-ins, and more * 3ds max is used to create approximately eighty percent of the top video games-including Grand Theft Auto 3-and is extensively employed for special effects in movies such as The Matrix Reloaded